Evidence of sustainable intensification in the production of palm oil from crops planted with Elaeis oleifera x Elaeis guineensis in Colombia - Mosquera-Montoya, Mauricio; Camperos, Jhonatan Eduardo; Ruiz, Elizabeth; Hernández, Diego; García, Alejandra; Vargas, Liseth Estefanía; Mesa, Eloina; Munévar, Daniel; Sinisterra, Kelly (Frontiers in Sustainable Food Systems, 2023)
Cultivars from crossings between Elaeis oleífera x Elaeis guineensis (OxG hybrids) have proven to have partial resistance to Bud Rot (BR), the most challenging disease for the Colombian palm oil agroindustry. Therefore, OxG hybrids were planted in areas that have experienced BR outbreaks since 2007. Soon, it was discovered that OxG hybrid female inflorescences required to be pollinated with pollen from E. guineensis to improve bunch formation. Researchers from Cenipalma noted that OxG hybrid bunches have a greater proportion of partenocarpic fruits. The latter generated a line of research that yielded artificial pollination in 2018. Artificial pollination consists of applying naphtaleneacetic acid (NAA) to female inflorescences in order to promote the formation of partenocarpic fruits. If artificial pollination was to be scaled up, many questions needed an answer such as, what was labor productivity, the stage at which bunches should be harvested and even, if it was profitable. This paper synthesizes the results of studies carried out by Cenipalma together with managers from oil palm plantations. These research studies were undertaken by means of time and motion studies, optimal harvesting time studies and cost-benefit analysis. Results come from plantations located at all the zones that have planted OxG cultivars that have planted the most common OxG hybrids. Our results indicate that an artificial pollination worker may be asked between 210 and 271 inflorescences per workday depending upon inflorescences density (inflorescences per hectare). We also found that by implementing criteria on harvest optimal stage one may increase the oil extraction rate from 5% to 15%. Finally, it was found that artificial pollination is more costly than using only E. guineensis pollen, but the increase in yields at the field and the increase in the amount of oil extracted offset this extra cost and provide greater profitability to oil palm growers. This is a sample of how, by using the same natural resources, implementing artificial pollination, and harvesting at the proper stage; one can have greater yields and have a more resilient business. In other words, this is an example of sustainable intensification.